2022
DOI: 10.1039/d1cs00948f
|View full text |Cite
|
Sign up to set email alerts
|

Ether-based electrolytes for sodium ion batteries

Abstract: This review summarizes the development history, basic characteristics, special co-intercalation mechanism, origin of the superior performance of ether-based electrolytes in sodium-ion batteries and their advancements in other batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
213
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 305 publications
(213 citation statements)
references
References 332 publications
0
213
0
Order By: Relevance
“…Furthermore, the ether-based electrolyte can realize thin, inorganic-rich SEI lm on the surface of the electrode and a relatively low specic surface of the electrode, which also helps to improve the ICE. 42 Besides, because the electrochemical reduction of Bi 2 O 3 is partially reversible, [43][44][45] high ICE is also proof of little Bi 2 O 3 content in the Bi-metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the ether-based electrolyte can realize thin, inorganic-rich SEI lm on the surface of the electrode and a relatively low specic surface of the electrode, which also helps to improve the ICE. 42 Besides, because the electrochemical reduction of Bi 2 O 3 is partially reversible, [43][44][45] high ICE is also proof of little Bi 2 O 3 content in the Bi-metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…The desolvation of Na + is not complete as it is normally found in the graphite-based anodes. 19,20,28 This fact can be deduced from the XRD results through the appearance and disappearance of a group of diffraction patterns observed between the discharge and charge processes. The schematic representation of the formation of Na x (dgm) 2 C 20 in a NGHSPC anode reflects the differences found with the typical Na + adsorption in NGHSPCs using carbonate-based electrolytes (Figure 5).…”
Section: Insights Of N-stage Formation In Nghspcsmentioning
confidence: 97%
“…Some changes of the G peak (the C−C stretching mode) have been associated to the formation of n-stage compounds during the Na + −ether co-intercalation reaction in graphite and hence to the graphitization index. 28,37 The Na test battery is a rich tool used to grasp changes in the chemical composition of materials such as in NGHSPCs, regardless of the typical electrochemical cycling behavior of different electrodes (Figure 3). Therefore, an unprecedented formation of n-stages in NGHSPC anodes is detected when utilizing the diglyme-based electrolyte in Na cells (Figures 4,BA, S2A−D, and S3).…”
Section: Insights Of N-stage Formation In Nghspcsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 185 ] Compared to the lower resistant against reduction for ester solvents (means more electrolyte decomposition and thick SEI formation), ether solvents show more stable reduction ability, leading to thin SEI formation and high ICE. [ 186 ] Generally, reports have revealed that carbon anodes using ether electrolyte possess higher ICE and better rate performance. [ 187 ] However, the cycling stability of carbon anodes in ester or ether electrolytes sometimes exists different results.…”
Section: Solid Electrolyte Interface In Carbon Anodesmentioning
confidence: 99%